Potentialities and deficiencies of qualitative research with families Potencialidades y debilidades de la investigación cualitativa con familias Potencialidades e debilidades da investigação qualitativa com famílias - Geisa dos Santos Luz; Silvana Sidney Costa Santos; Mara Regina Santos da Silva; Priscila Arruda da Silva (Universidad de Antioquia, 2012)
Objective. To analyze the literature relating to qualitative research about the theme family that was published in Brazilian nursing journals in the period from 2006 to 2010. Methodology. Research involving investigation of bibliographic databases of articles presenting descriptors like the following terms: family, qualitative research and nursing. Results. 47 articles were analyzed. The most frequent topic areas are: child health (40.4%), adult health (23.4%), mental health (19.1%), collective health (6.4%), elderly health (6.4%) and woman's health (4.3%). 70.6% of the articles were published in journals classified by QUALIS/ CAPES as B1. 93.6% of the articles were written by nurses with a doctorate degree. Data collection was predominantly carried out using semistructured (57.4%) and open interviews (39.8%). The interviews were followed by observation methods in 8.5% of the analyzed studies. Conclusion. The literature about qualitative studies that address the theme family which was published in Brazilian nursing journals during the study period is rare, which shows the need to further address the topic. Objetivo. Analizar la producción bibliográfica de los estudios cualitativos sobre el tema de la familia publicados en las revistas de enfermería brasileñas en el período 2006-2010. Metodología. Se consultó en las bases de datos bibliográficas los artículos que tuvieran como descriptores los términos: familia, investigación cualitativa y enfermería. Resultados. Se analizaron 47 artículos. Por áreas de atención, los más frecuentes son: salud del niño (40.4%), salud del adulto (23.4%), salud mental (19.1%), Salud colectiva (6.4%), salud del anciano (6.4%) y salud de la mujer (4.3%). El 70.6% de los artículos se publicaron en revistas clasificadas por QUALIS/CAPES como B1. El 93.6% de los artículos tenían por autores enfermeros con doctorado. Como instrumento de recolección de los datos predominaron la entrevista semi-estruturada (57.4%) y la abierta (30.8%). La conducción de las entrevistas fueron acompañadas de métodos observacionales en 8.5% de los estudios analizados. Conclusión. La producción bibliográfica de los estudios cualitativos sobre el tema de la familia publicados en las revistas de enfermería brasileñas en el período de estudio es escasa, mostrando que hay necesidad de un mayor desarrollo en la misma. Objetivo. Analisar a produção bibliográfica dos estudos qualitativos sobre o tema da família publicados nas revistas de enfermaria brasileiras no período 2006-2010. Metodologia. Investigação na que se conferiu nas bases de dados bibliográficas os artigos que tivessem como descritores os termos: família, investigação qualitativa e de enfermaria. Resultados. Analisaram-se 47 artigos. Por áreas de atendimento, os mais frequentes são: saúde da criança (40.4%), saúde do adulto (23.4%), saúde mental (19.1%), Saúde coletiva (6.4%), saúde do ancião (6.4%) e saúde da mulher (4.3%). O 70.6% dos artigos se publicaram em revistas classificadas por QUALIS/CAPES como B1. O 93.6% dos artigos tinham por autores enfermeiros com doutorado. Como instrumento de recolha dos dados predominaram a entrevista semiestruturada (57.4%) e a aberta (30.8%). A condução das entrevistas foram acompanhadas de métodos observacionais em 8.5% dos estudos analisados. Conclusão A produção bibliográfica dos estudos qualitativos sobre o tema da família publicados nas revistas de enfermaria brasileiras no período de estudo é escassa, mostrando que há necessidade de um maior desenvolvimento na mesma.